Современные направления планирования эксперимента процесса дробления с обработкой данных в системе STATISTICA - Костромицкий, Д. Ю.; Левченко, Э. П. (НТУ "ХПИ", 2010)
Наведені результати теоретичних досліджень, описання багатофакторного експерименту с подальшою математичною обробкою результатів, відомими методами математичної статики. Обробка даних двофакторного експерименту у системі STATISTICA.

Results of theoretical investigations, description of complex experiment from further mathematical processing of results with the help of well-known methods of mathematical statics are given. Data processing of bifactorial experiment in the system STATISTICA.
Keywords: дробильно-измельчительные машины; энергозатраты; методы математической статистики; моделирование процессов; дробление агломерата; технологический процесс дробления